PELAKSANAAN PEKERJAAN LAPIS FONDASI SEMEN KOMPOSIT TANAH PADA RUAS JALAN MERAUKE–TANAH MERAH - Osman H. Marbun; Asniaty .; Arnold Mika; Dameria Hutagalung (Jurnal HPJI (Himpunan Pengembangan Jalan Indonesia), 2020)
Abstract The Merauke–Tanah Merah Road section is a road linking Merauke Regency and Boven Digoel Regency, Papua Province. The type of soil that exists along the road section is alluvial soil, which has a high potential for shrinkage due to changes in water content. In road construction, this type of soil falls into the category of problematic soil, which needs to be stabilized before it is used as a road sub base layer. The construction of a soil composite cement foundation layer is a foundation layer made of soil stabilized with cement, added with certain additives. The use of the additive was intended to reduce cement content and increase the Unconfined Compression Strength and durability of the cement soil produced. This study uses Matos additive material, which serves to compact or solidify and stabilize the soil physically and chemically. The results of the implementation in the field showed that there was an increase in the strength of the Subbase Composite Cement Base Layer using Matos as additives. However, the use of this additive material needs to be studied in more depth by taking into account the increase in the average of unconfined compression strength, which is only about 6%, while the cost increases by around 54%. Keywords: foundation layers, alluvial soils, road construction, soil stabilization, additives  Abstrak Ruas Jalan Merauke–Tanah Merah merupakan ruas jalan yang menghubungkan Kabupaten Merauke dan Kabupaten Boven Digoel, Provinsi Papua. Jenis tanah yang ada di sepanjang ruas jalan tersebut adalah tanah aluvial, yang memiliki potensi kembang-susut tinggi akibat perubahan kadar air. Dalam pekerjaan konstruksi jalan, jenis tanah ini masuk dalam kategori tanah yang bermasalah, sehingga perlu distabilisasi sebelum digunakan sebagai lapis fondasi jalan. Konstruksi lapis fondasi semen komposit tanah merupakan lapis fondasi yang terbuat dari tanah yang distabilisasi dengan semen, ditambah dengan bahan tambah tertentu. Penggunaan bahan tambah berfungsi mengurangi kadar semen dan meningkatkan kuat tekan bebas serta durabilitas tanah semen yang dihasilkan. Pada kajian ini digunakan bahan tambah Matos, yang berfungsi untuk memadatkan atau solidifikasi dan menstabilkan tanah secara fisik-kimia. Hasil pelaksanaan di lapangan menunjukkan bahwa terjadi peningkatan kekuatan Lapis Fondasi Semen Komposit Tanah yang menggunakan bahan tambah Matos. Walaupun demikian, penggunaan bahan tambah ini perlu dikaji secara lebih mendalam dengan memperhatikan peningkatan kuat tekan bebas rata-rata yang hanya sekitar 6%, sedangkan biayanya meningkat sekitar 54%. Kata-kata kunci: lapis fondasi, tanah aluvial, konstruksi jalan, stabilisasi tanah, bahan tambah